Housing, Imputed Rent, and Households' Welfare - Ceriani, Lidia (World Bank, Washington, DC, 2019)
Housing is the largest durable good consumed by households. As such, any consumption-based measure of welfare, to be comprehensive, must include the value of the flow of services households derive from their dwellings, the so-called imputed rent. However, estimating imputed rents is a daunting task, which researchers and practitioners tend to overlook. This paper is the first attempt to assess the distributional impact of including housing in the welfare aggregate; the paper tests two estimation methods and analyzes four developing countries. The distributional impact cannot be predicted a priori, and evidence suggests it is context and method specific. Although changes in poverty and inequality are always statistically significant, they are only occasionally larger than one percentage point. By contrast, shared prosperity exhibits sizable changes, which might also determine international re-rankings. Albeit the inclusion of imputed rents reshuffles the set of poor households, observed changes in the socioeconomic profiling of the poor are unlikely to affect pro-poor policy design.